Fat in sow diets: effects on rebreeding and subsequent litter size - Pollmann, D.S.; Allee, G.L.; Schoenherr, W.D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two on-farm trials with a total of 264 sows were conducted to evaluate the effects of added fat in the diet during the last seven days of lactation and/or during the period from weaning to remating on days from weaning to first service and to evaluate the effects of added fat prior to breeding on subsequent litter size. In Trial 1, by feeding sows 1 pound of fat 7 days prior to weaning litters and 7 days postweaning did not improve rebreeding performance. The subsequent farrowing rate was not affected by the fat addition but there was a slight improvement in farrowing rate for gilts (24 vs. 33%). The fat addition tended to increase the size of the farrowing litter by .9 pig. In Trial 2, adding 1 pound of fat daily to the feed from weaning until first service did not improve rebreeding performance. Fat addition did not affect subsequent litter size.
Keywords: Swine; Sow; Rebreeding; Litter size